The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnut.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Selenium and Glutathione as Antiviral Factors in COVID-19: Does the Viral Mpro Protease Target Host Selenoproteins and Glutathione Synthesis?

Abstract: Glutathione peroxidases (GPX), a family of antioxidant selenoenzymes, functionally link selenium and glutathione, which both show correlations with clinical outcomes in COVID-19. Thus, it is highly significant that cytosolic GPX1 has been shown to interact with an inactive C145A mutant of M pro , the main cysteine protease of SARS-CoV-2, but not with catalytically active wild-type M pro . This seemingly anomalous result is what might be expected if GPX1 is a substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 35 publications
(45 reference statements)
1
75
0
Order By: Relevance
“…The relatively higher accessibilities of cleavage sites are in agreement with the susceptibilities of CTBP1 and IRAK1 for proteolysis in vitro ( Figure 5 ) and indicate that probabilities of cleavage sites predicted by the NetCorona webserver need to be interpreted by considering surface accessibilities of putative sites, as well. Our result highlights that determination of apparent accessibilities of cleavage sites in the protein structures is not sufficient enough ( Figure 2 ); in agreement with the results of Taylor and Radding [ 29 ], we also suggest the detailed determination of structural characteristics, especially the calculation of numerical SASA values ( Figure 7 ) for more reliable cleavage site prediction.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The relatively higher accessibilities of cleavage sites are in agreement with the susceptibilities of CTBP1 and IRAK1 for proteolysis in vitro ( Figure 5 ) and indicate that probabilities of cleavage sites predicted by the NetCorona webserver need to be interpreted by considering surface accessibilities of putative sites, as well. Our result highlights that determination of apparent accessibilities of cleavage sites in the protein structures is not sufficient enough ( Figure 2 ); in agreement with the results of Taylor and Radding [ 29 ], we also suggest the detailed determination of structural characteristics, especially the calculation of numerical SASA values ( Figure 7 ) for more reliable cleavage site prediction.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, we assumed that structural contexts of the putative cleavage sites need to be considered, therefore, accessibilities of target regions were also determined. A similar in silico approach has already been applied for the identification of potential cleavage sites in host selenoproteins and enzymes of glutathione synthesis [ 29 ], but neither proteomic [ 21 ] nor specifically targeted analyses proved cleavages of these targets in vitro to date. Interestingly, PAI2 was identified as a substrate of SARS-CoV and hCoV-NL63 3CLpro, as well, while cleavage of PLMN was not detected by a proteomic analysis [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is interesting in light of a recent report that SELENOF may be targeted for proteolysis by the SARS-CoV-2 main protease M pro , because the SELENOF protein contains a sequence (TVLQ/AVSA) that is almost identical to a known viral M pro cleavage site (TVLQ/AVGA). 16 Taken together, these observations suggest that disruption of SELENOF function may be particularly important for SARS-CoV-2 replication.…”
Section: Resultsmentioning
confidence: 85%
“…Regarding selenium, Taylor and Radding ( 55 ) mentioned that the resulting collateral damage due to increased oxidative stress and inflammation would be exacerbated by dietary deficiency of selenium and GSH precursors. In the review by Hiffler and Rakotoambinina ( 39 ), it was observed that low-selenium status is common in individuals considered at risk of developing severe COVID-19, particularly in the elderly.…”
Section: Discussionmentioning
confidence: 99%